1987
DOI: 10.1007/bf00610380
|View full text |Cite
|
Sign up to set email alerts
|

Effect of drugs on oro-caecal transit time assessed by the lactulose/breath hydrogen method

Abstract: The comparative actions of two benzamides; the one metoclopramide, having and the other, BRL 20627, lacking dopamine receptor antagonist properties have been investigated on orocaecal transit time (OCTT) using the lactulose/breath hydrogen method. In addition, the action of codeine, propantheline and domperidone on OCTT has been assessed. Similar quantitative reductions in apparent OCTT were found with metoclopramide and BRL 20627 thus, metoclopramide 20 mg orally and 10 mg i.v. brought about 32.5% and 42% red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

1990
1990
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 14 publications
1
10
0
Order By: Relevance
“…Validation studies have confirmed a high degree of correlation with simultaneous scintigraphy (19-22). Lactulose breath tests have been used to document pharmacological effects on gut motility (23-27) and to study disease states in adults and in children (28-33). …”
Section: Evaluation Of Small Bowel Transitmentioning
confidence: 99%
“…Validation studies have confirmed a high degree of correlation with simultaneous scintigraphy (19-22). Lactulose breath tests have been used to document pharmacological effects on gut motility (23-27) and to study disease states in adults and in children (28-33). …”
Section: Evaluation Of Small Bowel Transitmentioning
confidence: 99%
“…A close and linear relationship between this procedure and radiological evaluation of small bowel transit time following a barium meal has been described [9]. Its application in children has been investigated lately [3,18,26,28] and the effect of several disorders [1,4,23,26] and a variety of drugs [24] on OCTT have been reported in children and adults. To date there are no publications on the use of the lactulose hydrogen breath test in patients with Crohn disease (CD) although small bowel transit time is delayed on upper gastrointes-…”
Section: Introductionmentioning
confidence: 97%
“…The lactulose/breath hydrogen test has been used to evaluate the effects of drugs on orocaecal transit time [16], but lactulose artificially reduces the transit time [17], and the measurement of hydrogen concentrations in expired breath samples is difficult. Staniforth has shown that mean orocaecal transit time was significantly shorter as measured by the lactulose/breath hydrogen test than by the sulphasalazinesulphapyridine method [17].…”
Section: Discussionmentioning
confidence: 99%